Variability of Dosing and Number of Medications Needed to Achieve Adequate Sedation in Mechanically Ventilated Pediatric Intensive Care Patients - Emma M. Tillman; Joseph Ipe; Kelly J. Weaver; Todd C. Skaar; Courtney M. Rowan; James E. Slaven (Wiley, 2021)
Children admitted to the pediatric intensive care unit (PICU) often require multiple medications to achieve comfort and sedation. Although starting doses are available, these medications are typically titrated to the desired effect. Both oversedation and undersedation are associated with adverse events. The aim of this retrospective study was to evaluate cumulative medication burden necessary to achieve comfort in patients in the PICU and determine relevant predictors of medication needs. In order to account for all of the sedative medications, z‐scores were used to assess the population average dose of each medication and compare each patient day to this population average. Sedation regimens for 130 patients in the PICU were evaluated. Mean overall infusion rates of fentanyl, morphine, and hydromorphone were 1.67 ± 0.81 µg/kg/hour, 0.12 ± 0.08 mg/kg/hour, and 17.84 ± 13.4 µg/kg/hour, respectively. The mean infusion rate of dexmedetomidine was 0.59 ± 0.28 µg/kg/hour, and midazolam was 0.14 ± 0.1 mg/kg/hour. Summation z‐sores were used to rank the amount of sedation medication needed to achieve comfort for each individual patient for his/her PICU stay in relation to the entire sample. Patient age, weight, and length of mechanical ventilation were all significant predictors of sedation requirement. This study will provide data necessary to develop a model of cumulative medication burden needed to achieve appropriate sedation in this population. This descriptive model in appropriately ranking patients based on sedative needs is the first step in exploring potential genetic factors that may provide an insight into homing in on the appropriate sedation regimen.